A 3D printed waterproof sunscreen mask and method
Through the combination of one-step printing technology and polymer materials, a 3D-printed waterproof and sunscreen mask with good breathability and comfort in wearing was prepared, which solved the problems of poor breathability and low production efficiency of existing masks, and achieved the fit between the mask and the user's facial contour and waterproof and sunscreen effects.
Patent Information
- Application Number
- CN202411783999.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing waterproof and sunscreen masks are poorly breathable and uncomfortable to wear when used. The traditional 3D printing technology only replaces the traditional textile processing method, which cannot avoid the influence of subsequent coating processes, resulting in poor economical and processing convenience.
3D printed waterproof sunscreen masks are prepared through one-step printing technology, and polymer material powders such as thermoplastic polyurethane and modified titanium dioxide or zinc oxide powder are used, combined with the gradient printing technology of 3D printers, masks with elastic structural surfaces and lattice structural surfaces are prepared. Multiple air ducts are provided on the lattice structural surface to improve breathability.
It achieves the fit between the mask and the user's facial contour, has good breathability and wear comfort, and has waterproof and sun protection effects, avoiding the needs of subsequent decoration processes and improving production efficiency and product performance.
Smart Images

Figure CN119745143A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing, and in particular relates to a 3D printing waterproof sunscreen mask and a method thereof. Background Art
[0002] Facial waterproof and sunscreen products have a wide range of demands and applications in different scenarios of life. For example, in daily work, such as riding electric bicycles and bicycles to and from work, the face is exposed to the sun for a long time; in outdoor sports and fitness, such as cycling, running, climbing, etc., long-term exposure to the sun will darken the skin and accelerate skin aging. At the same time, as the body temperature rises, excessive water loss leads to serious consequences such as heat stroke or heat stroke. Therefore, sunscreen masks and face masks have gradually become necessities in people's lives. At the same time, with the continuous development of manufacturing technology, the functional requirements for facial sunscreen products are also increasing. For example, in different rainy and snowy weather and long-term outdoor activities, waterproof and breathable properties have also become a must; when worn, they need to stay dry for a long time to ensure smooth breathing and comfort. At the same time, facing people with higher professional requirements, such as professional athletes in outdoor sports, it is necessary to tailor customized facial appliances that conform to facial contours according to ergonomic principles, sports scenes and personal special needs.
[0003] At present, most masks on the market are still processed by traditional textile technology. Due to the fixed production lines and raw materials, customized small-batch product development is rare and the cost of iterative updates is high. For sun protection facial appliances, the existing protective masks are mainly made of textile materials such as polyester and nylon, and mainly rely on the addition of sunscreen to achieve physical sun protection. Physical sun protection uses reflective particles and physical covering to block, reflect or scatter ultraviolet rays, so that the amount of ultraviolet rays reaching the skin can be reduced to achieve the purpose of sun protection. Although it has a certain sun protection effect, masks made of polyester and nylon will become stuffy when used, some masks do not stick to the user's face, and the use effect is poor after multiple washings. They are not waterproof, and the mask is soaked after high-frequency exercise, causing discomfort on the face. And as bacteria and pollutants accumulate on the surface of the mask, stains are formed, which will seriously reduce the service life and wearing experience of the protective mask.
[0004] Therefore, in order to meet higher customization needs, some companies have tried to use 3D printing technology to develop facial appliances that conform to facial contours. As an emerging processing and production method in recent years, 3D printing has unique advantages different from traditional processing methods. It can process metal and non-metal materials, including plastic products commonly used in daily life, usually using polymer materials such as polylactic acid (PLA), thermoplastic polyurethane (TPU) and nylon (PA); it does not require mold opening, and can achieve many complex structures that cannot be processed by traditional processing methods, such as hollow lattice structures that cannot be made by traditional molds. 3D printing uses a stacking processing method, and there is no problem of being unable to process; and 3D printing completes product production in one step, with a simple process and does not require a large amount of manpower, which is suitable for small-batch flexible production. 3D printing technology includes selective laser sintering (SLS) printing technology, fused deposition modeling (FDM) printing technology, and selective curing of photosensitive resin (SLA) printing technology. As a mature 3D printing processing method, SLS uses software to slice the three-dimensional model of the part along the Z direction, set the preheating temperature, scanning rate, scanning power, single layer thickness and other process parameters, and then use a powder roller to spread a layer of powder material on the workbench. The laser beam emitted by the laser selectively scans the powder layer under the control of the computer according to the data of each section of the geometric shape. In the area scanned by the laser, the powder junction melts and the powders adhere to each other. The part not irradiated by the laser is still loose, serving as a support for the work and the next layer of powder; after one layer is sintered, the workbench drops the height of a cross-section layer, and then the next layer of powder is spread and sintered, and the cycle is repeated to obtain the designed three-dimensional solid parts. Its characteristics are that the size and shape can be customized without support, and personalized products can be designed without considering the placement angle, etc. At the same time, through structural design and parameter design, gradient changes in the structure of printed products can be achieved, thereby realizing functional gradient products.
[0005] The 3D printed waterproof and / or sunscreen masks that have been reported and developed are very similar to traditional masks. The difference is that 3D printing technology is used as a substitute, and there is not much innovation and improvement in terms of functionality. After the mask is made by 3D printing of conventional elastomers, a surface treatment agent or coating with waterproof or sunscreen effect is attached to the surface of the mask through a surface finishing process to achieve a sunscreen effect, which is similar to the processing method of traditional fabrics. Commonly used sunscreens are also called physical shielding agents. They mainly add inorganic particles such as titanium dioxide (TiO2) and zinc oxide (ZnO) into surface finishing agents or coatings, and evenly apply them on the surface of the facial appliance body to form a physical sunscreen protective layer. The protective layer reflects, refracts and scatters ultraviolet rays to shield part of the damage to the skin from ultraviolet rays.
[0006] The titanium dioxide used is commonly known as titanium dioxide. It is insoluble in water and organic solvents. It blocks ultraviolet UVB and part of UVA by reflection and scattering. It has good ultraviolet absorption performance, which is due to its special electronic structure. In the crystal structure of titanium dioxide, titanium atoms and oxygen atoms form a three-dimensional network structure. In this structure, there are covalent bonds and ionic bonds between titanium atoms and oxygen atoms. When ultraviolet rays irradiate the surface of titanium dioxide, it excites the electrons in titanium dioxide. These excited electrons will jump to a higher energy level and form an excited state. In the excited state, titanium dioxide will undergo a series of interactions between electrons and atoms, thereby converting ultraviolet energy into other forms of energy. Ultimately, titanium dioxide will convert ultraviolet energy into heat energy, which is absorbed. Zinc oxide is also an important and widely used physical sunscreen. Zinc oxide can block radiation in the ultraviolet UVA and UVB bands, and is safe and non-irritating. Zinc oxide is insoluble in water and has a high degree of safety. Zinc oxide is an N-type semiconductor. The electrons in the valence band can accept the energy in ultraviolet rays and make transitions, which is also the principle of their absorption of ultraviolet rays. The function of scattering ultraviolet rays is related to the particle size of the material. When the size is smaller than the wavelength of ultraviolet rays, the particles can scatter the ultraviolet rays acting on them in all directions, thereby reducing the intensity of ultraviolet rays in the irradiation direction. Zinc oxide is a stable compound that can provide broad-spectrum ultraviolet protection (UVA and UVB), and also has antibacterial and anti-inflammatory effects. It is the safest and most effective ingredient in the evaluation of sunscreens in almost all countries. Titanium dioxide can protect against ultraviolet rays in the band of 250 to 340, and zinc oxide can protect against ultraviolet rays in the band of 290 to 380. Titanium dioxide absorbs UVB more effectively, and its resistance to UVA with a wavelength above 350nm is getting weaker and weaker. More than 90% of ultraviolet rays are UVA, and they will have different penetration when irradiated on the skin. UVB can reach the epidermis of the skin, while UVA can reach the dermis of the skin. Compared with titanium dioxide, zinc oxide absorbs UVB less, but absorbs UVA above 350nm more strongly.
[0007] Although waterproof and sunscreen masks processed by traditional processing methods and existing 3D printing can meet customization needs and achieve functionality, due to the limitations of the subsequent traditional coating process, these masks are not breathable when used, affecting the comfort of wearing and not suitable for long-term use. The 3D printing technology currently used in waterproof and sunscreen masks has only replaced the traditional textile processing method. The rapid prototyping processing method of 3D printing integrated molding can meet small-batch customization needs, but it cannot avoid the impact of subsequent coating and finishing processes. There is not much improvement in terms of economy and processing convenience. At the same time, the mask has poor air permeability and is not suitable for long-term wear. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a 3D printed waterproof sunscreen mask and method, the purpose of which is to use 3D printing technology to make a waterproof sunscreen mask through one-step printing. The obtained mask better fits the user's facial contour, has good air permeability, is comfortable to wear, and can also play a waterproof and sunscreen effect.
[0009] In order to achieve the above object, the present invention provides a method for 3D printing a waterproof sunscreen mask, comprising the following steps:
[0010] Step S1, designing a mask, using an instrument to scan the user's facial contour to obtain facial information, designing a mask that fits the user's face in the software, adjusting the size, and editing to obtain a mask that fits the user's face;
[0011] Step S2, printing preparation, preparing printing powder, stirring and blending the printing powder with a stirrer to obtain a mixed powder, determining whether the mixed powder meets the printing requirements, and then printing a test piece on a 3D printer, adding the mixed powder to the printer, spreading the mixed powder evenly in the printer, arranging the sample in the printer, starting to print the test piece using energy density, and testing the printed test piece;
[0012] Step S3, adjusting printing parameters, adding polymer material powder into the printer, spreading the powder evenly in the printer, arranging the test sample into 5 layers in the printer, adjusting printing parameters, starting to print the polymer material test piece, and testing the printed polymer material test piece;
[0013] Step S4, printing the mask, adding the printing powder into the powder feeding cylinder and compacting it, closing the printer, filling with nitrogen, adjusting different printing parameters according to the characteristics of different areas of the mask, and starting gradient printing of the mask after the nitrogen filling is completed. After the printing is completed, the mask is taken out of the printer, and the remaining powder on the surface of the mask is cleaned, and the mask is put into the sandblasting machine for sandblasting. After the cleaning is completed, a 3D printed waterproof and sunscreen mask is obtained.
[0014] Further, in step S1, the instrument is a 3D contour scanner; the software is the three-dimensional software Rhino;
[0015] In step S2, the powder is stirred and blended with a stirrer for 30 to 60 minutes; the repose angle and rolling angle of the mixed powder must meet the printing fluidity requirements; the size of the sample is 80*50*2mm; the energy density is 0.35 to 0.55j / mm3;
[0016] In step S3, the polymer material powder is thermoplastic polyurethane elastomer powder; the size of the test sample is 10*10*10mm; the printing parameters include laser power, scanning spacing, printing layer thickness and scanning rate, etc.;
[0017] In step S4, the time for sandblasting in the sandblasting machine is 15 minutes.
[0018] Furthermore, in step S2, when the printing powder is titanium dioxide powder and thermoplastic polyurethane elastomer powder, the titanium dioxide powder accounts for 1 to 5% of the mixed powder; when the printing powder is zinc oxide powder and thermoplastic polyurethane elastomer powder, the zinc oxide powder accounts for 1 to 5% of the mixed powder; when the printing powder is treated modified zinc oxide powder, modified titanium dioxide powder and thermoplastic polyurethane elastomer powder, the modified zinc oxide powder and modified titanium dioxide powder each account for 1 to 5% of the mixed powder.
[0019] Furthermore, when the printing powder is a treated modified zinc oxide powder, a modified titanium dioxide powder and a thermoplastic polyurethane elastomer powder, the treatment method is to add the titanium dioxide powder or zinc oxide powder to an ethanol aqueous solution, ultrasonically treat and stir, add a coupling agent dropwise and maintain, then stir, condense and reflux, wash the obtained product with distilled water, filter it 3 times, and vacuum dry it at 60°C for 24 hours to constant weight to obtain a surface functionalized titanium dioxide powder or zinc oxide powder; put the dried titanium dioxide powder or zinc oxide powder into a ball mill for ball milling, and sieve the titanium dioxide powder or zinc oxide powder obtained by ball milling with a fine sieve to obtain a surface-modified titanium dioxide powder or zinc oxide powder with a particle size of 10 to 100 μm;
[0020] The thermoplastic polyurethane elastomer powder is placed in a drying oven for drying, and then the dried thermoplastic polyurethane elastomer powder is placed in a ball mill for ball milling; then the obtained thermoplastic polyurethane elastomer powder is sieved with a fine sieve to obtain a thermoplastic polyurethane elastomer powder with a particle size of 20 to 100 μm.
[0021] Furthermore, after adding the coupling agent, the temperature is maintained at 70-80°C for 3-6 hours; the temperature of stirring, condensing and reflux is 70°C, and the time is 3-6 hours; the coupling agent is a silane coupling agent KH550, and the mass ratio of silane coupling agent: water: anhydrous ethanol is 1:2:50; the titanium dioxide powder or zinc oxide powder is put into the ball mill at a ball mill speed of 400r / min, and the ball milling time is 30-60min; the thermoplastic polyurethane elastomer powder is put into a drying oven for drying treatment at a drying temperature of 40-60°C, and the drying time is 10-30min; the thermoplastic polyurethane elastomer powder is put into the ball mill at a ball mill speed of 400r / min, and the ball milling time is 10-30min.
[0022] The present invention also provides a 3D printed waterproof sunscreen mask, which is made by the above-mentioned method of 3D printing waterproof sunscreen mask, and includes an elastic structure surface and a lattice structure surface; the lattice structure surface is arranged on the elastic structure surface; a plurality of air ducts are arranged in the lattice structure surface; and the lattice structure surface can fit the surface of the human body.
[0023] The invention discloses a 3D printed waterproof sunscreen mask, which is obtained by printing waterproof sunscreen materials in a 3D printer and has the functions of waterproof sunscreen. The mask mainly comprises an elastic structure surface and a lattice structure surface. The elastic structure surface is exposed to the external air and has a good air permeability effect. The elastic structure surface is provided with a lattice structure surface, which can fit the surface of the human body and improve the wearing comfort. At the same time, a plurality of air ducts are provided in the lattice structure surface, which can promote the circulation of air and the circulation of gas exhaled and inhaled through the mouth and nose, thereby improving the air permeability.
[0024] Furthermore, the elastic structural surface includes an outer structural surface and an inner structural surface; the outer structural surface and the inner structural surface are tightly fitted; the inner structural surface is cut to obtain a cutting area; the lattice structural surface is arranged on the cutting area; and the inner structural surface is in direct contact with human skin.
[0025] The elastic structure surface includes an outer structure surface and an inner structure surface. The outer structure surface is directly in contact with the outside air and has good air permeability. The inner structure surface is in direct contact with human skin and has good surface finish. The inner structure surface is cut to obtain a cutting area. The lattice structure surface provided in the cutting area also has good air permeability. Except for the cutting area, the other parts have relatively low requirements for air permeability.
[0026] Furthermore, the lattice structure surface includes a first lattice structure surface and a second lattice structure surface; the first lattice structure surface and the second lattice structure surface are arranged opposite to each other; the first lattice structure surface and the second lattice structure surface are arranged at two ends of the inner structure surface; the first lattice structure surface is in contact with the human nose; and the second lattice structure surface is in contact with the human chin.
[0027] The arrangement of the first lattice structure surface and the second lattice structure surface enables the 3D printed waterproof sunscreen mask to fit the human body surface well, improving the wearing comfort. The first lattice structure surface contacts the human nose, providing a better movement space for the human nose, preventing the mask from pressing the nose, and improving the wearing comfort. The second lattice structure surface contacts the human chin, providing a better movement space for the human chin, preventing the mask from pressing the chin, and improving the wearing comfort.
[0028] Furthermore, the elastic structural surface also includes fixing belts; the fixing belts are arranged at both ends of the outer structural surface.
[0029] The elastic structural surface also includes a fixing strap, which can fix the mask on the human ear to realize the wearing of the 3D printed waterproof sunscreen mask.
[0030] Furthermore, the air permeability of the outer structural surface is higher than the air permeability of the inner structural surface.
[0031] The outer structural surface is the overall structural surface of the 3D printed waterproof sunscreen mask, and the breathability effect should be obvious. The inner structural surface is cut, and a lattice structural surface is provided in the cutting area. The lattice structural surface is breathable through multiple air ducts. Except for the cutting area, the other parts have relatively low requirements for breathability.
[0032] Beneficial Effects
[0033] 1. The method for 3D printing a waterproof sunscreen mask of the present invention can produce a waterproof sunscreen mask through one-step printing, and no additional finishing process is required afterwards;
[0034] 2. The 3D printed waterproof sunscreen mask of the present invention can better fit the facial contour of the user;
[0035] 3. The 3D printed waterproof sunscreen mask of the present invention has good air permeability and is comfortable to wear;
[0036] 4. The 3D printed waterproof sunscreen mask of the present invention also has the functions of waterproofing and sunscreening. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic diagram of the structure of a 3D printed waterproof sunscreen mask;
[0038] Figure 2 This is the front view of the 3D printed waterproof sunscreen mask;
[0039] Figure 3 Side view of the 3D printed waterproof sunscreen mask.
[0040] In the accompanying drawings: 1, elastic structure surface; 2, lattice structure surface; 11, outer layer structure surface; 12, inner layer structure surface; 13, fixing belt; 21, first lattice structure surface; 22, second lattice structure surface. DETAILED DESCRIPTION
[0041] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0042] Example 1
[0043] like Figures 1 to 3 A 3D printed waterproof sunscreen mask is shown, comprising an elastic structure surface 1 and a lattice structure surface 2; the lattice structure surface 2 is arranged on the elastic structure surface 1; a plurality of air ducts are arranged in the lattice structure surface 2; the lattice structure surface 2 can fit the surface of the human body.
[0044] A 3D printed waterproof sunscreen mask is obtained by printing waterproof and sunscreen materials in a 3D printer. The mask has the functions of waterproof and sunscreen. The mask mainly comprises an elastic structure surface 1 and a lattice structure surface 2. The elastic structure surface 1 is exposed to the outside air and has a good air permeability effect. The elastic structure surface 1 is provided with a lattice structure surface 2. The lattice structure surface 2 can fit the surface of the human body to improve the wearing comfort. At the same time, a plurality of air ducts are provided in the lattice structure surface 2 to promote the circulation of air, promote the circulation of gas exhaled and inhaled through the mouth and nose, and improve the air permeability.
[0045] The elastic structure surface 1 includes an outer structure surface 11 and an inner structure surface 12; the outer structure surface 11 and the inner structure surface 12 are tightly fitted; the inner structure surface 12 is cut to obtain a cutting area; the lattice structure surface 2 is arranged on the cutting area; the inner structure surface 12 is in direct contact with human skin.
[0046] The elastic structure surface 1 includes an outer structure surface 11 and an inner structure surface 12. The outer structure surface 11 is directly in contact with the outside air and has good air permeability. The inner structure surface 12 is in direct contact with human skin and has good surface finish. The inner structure surface 12 is cut to obtain a cutting area. The lattice structure surface 2 provided in the cutting area also has good air permeability. Except for the cutting area, the other parts have relatively low requirements for air permeability.
[0047] The lattice structure plane 2 includes a first lattice structure plane 21 and a second lattice structure plane 22; the first lattice structure plane 21 and the second lattice structure plane 22 are arranged opposite to each other; the first lattice structure plane 21 and the second lattice structure plane 22 are arranged at two ends of the inner structure plane 12; the first lattice structure plane 21 contacts the human nose; the second lattice structure plane 22 contacts the human chin.
[0048] The arrangement of the first lattice structure surface 21 and the second lattice structure surface 22 enables the 3D printed waterproof sunscreen mask to fit the human body surface well, improving the wearing comfort. The first lattice structure surface 21 contacts the human nose, providing a better movement space for the human nose, preventing the mask from pressing the nose, and improving the wearing comfort. The second lattice structure surface 22 contacts the human chin, providing a better movement space for the human chin, preventing the mask from pressing the chin, and improving the wearing comfort.
[0049] The elastic structural surface 1 further includes fixing belts 13 ; the fixing belts 13 are arranged at both ends of the outer structural surface 11 .
[0050] The elastic structural surface 1 also includes a fixing belt 13, which can fix the mask on the human ear to realize the wearing of the 3D printed waterproof sunscreen mask.
[0051] The air permeability of the outer structural surface 11 is higher than that of the inner structural surface 12 .
[0052] The outer structural surface 11 is the overall structural surface of the 3D printed waterproof sunscreen mask, and the breathability effect is obvious. The inner structural surface 12 is cut, and the cutting area is provided with a lattice structural surface 2. The lattice structural surface 2 is breathable through multiple air ducts. Except for the cutting area, the other parts have relatively low requirements for breathability.
[0053] Example 2
[0054] A 3D printed UVB protection mask comprises the following steps:
[0055] Step S1, designing a mask, using a 3D contour scanner to scan the user's facial contour to obtain facial information, designing a mask that fits the user's face in the three-dimensional software Rhino, adjusting the size, and editing to obtain a mask that fits the user's face;
[0056] Step S2, printing preparation, weighing 250g of titanium dioxide (TiO2) powder and 4750g of thermoplastic polyurethane elastomer (TPU) powder, stirring and blending a total of 5000g of powder with a stirrer for 30min, so that the titanium dioxide powder and the thermoplastic polyurethane elastomer (TPU) powder are fully and evenly stirred, and a mixed powder containing 5% titanium dioxide (TiO2) is obtained after stirring evenly, and the mixed powder is added to the printer, and the mixed powder is evenly spread in the printer, and a sample with a size of 80*50*2mm is arranged in the printer, and an energy density of 0.45j / mm3 is used to start printing a test piece, and the printed test piece is tested. The test results show that the test piece with 5% titanium dioxide (TiO2) powder added has a sun protection level SPF value of 30, which is much greater than the test piece without titanium dioxide (TiO2) powder, and other basic performance tests do not show a significant reduction in strength;
[0057] Step S3, printing parameter adjustment, add 5000g of thermoplastic polyurethane elastomer (TPU) powder into the printer, spread the powder evenly in the printer, divide the test sample into 5 layers and arrange it in the printer, adjust the printing parameters such as laser power of 48W, scanning spacing of 0.12mm, printing layer thickness of 0.2mm and scanning rate, etc., and adjust the scanning rate so that each layer uses energy density of 0.35, 0.4, 0.45, 0.5, and 0.55j / mm3 respectively, start printing the thermoplastic polyurethane elastomer (TPU) test piece, and test the printed thermoplastic polyurethane elastomer (TPU) test piece; use the mercury injection method to test the porosity of the thermoplastic polyurethane elastomer (TPU) test piece at different energy densities, and find that the porosity decreases with the increase of energy density. Therefore, by adjusting the scanning rate to control the energy density, it is possible to print thermoplastic polyurethane elastomer (TPU) parts with different porosities. The thermoplastic polyurethane elastomer (TPU) test piece with higher porosity shows better air permeability.
[0058] Step S4, printing the mask, adding 250g of titanium dioxide (TiO2) powder and 4750g of thermoplastic polyurethane elastomer (TPU) powder into the powder feeding cylinder for compaction, closing the printer, filling with nitrogen, adjusting the printing parameters, the outer structural surface is the overall structural surface of the mask, the ventilation effect should be obvious, setting the laser power of the outer structural surface to 48W, the scanning spacing to 0.12mm, the printing layer thickness to 0.2mm, and the scanning rate to 4444mm / s; the inner structural surface is cut, and the cutting area is provided with a lattice structural surface, and the lattice structural surface is breathable through multiple air ducts. Except for the part in the cutting area, the other parts have relatively low requirements for air permeability, and the inner structural surface is in direct contact with human skin, so it is necessary to ensure the surface smoothness of the mask, and set the laser power of the inner structural surface to 48W, the scanning spacing to 0.12mm, the printing layer thickness to 0.2mm, and the scanning rate to 4444mm / s. The power is 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 4000mm / s; the lattice structure surface can fit the human body surface well, is comfortable, and can avoid the mask from squeezing the nose and chin. The lattice structure surface is provided with multiple air ducts to promote air circulation and achieve breathability. Therefore, the lattice structure surface does not need to consider the porosity. The laser power of the lattice structure surface is set to 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 3636mm / s. After the nitrogen filling is completed, the mask is printed. After the printing is completed, the mask is taken out of the printer, and the remaining powder on the surface of the mask is cleaned, and it is put into the sandblasting machine for sandblasting for 15 minutes. After the cleaning is completed, a 3D printed UVB-proof mask is obtained.
[0059] Example 3
[0060] A 3D printed UVA protection mask comprises the following steps:
[0061] Step S1, designing a mask, using a 3D contour scanner to scan the user's facial contour to obtain facial information, designing a mask that fits the user's face in the three-dimensional software Rhino, adjusting the size, and editing to obtain a mask that fits the user's face;
[0062] Step S2, printing preparation, weighing 250g zinc oxide (ZnO) powder and 4750g thermoplastic polyurethane elastomer (TPU) powder, stirring and blending a total of 5000g of powder with a stirrer for 30min, so that the zinc oxide (ZnO) powder and the thermoplastic polyurethane elastomer (TPU) powder are fully and evenly stirred, and a mixed powder containing 5% zinc oxide (ZnO) is obtained after stirring evenly, and the mixed powder is added to the printer, and the mixed powder is evenly spread in the printer, and a sample with a size of 80*50*2mm is arranged in the printer, and an energy density of 0.45j / mm3 is used to start printing a test piece, and the printed test piece is tested. The test results show that the test piece with 5% zinc oxide (ZnO) powder added has a sun protection level SPF value of 28, which is much greater than the test piece without zinc oxide (ZnO) powder, and other basic performance tests do not show a significant reduction in strength;
[0063] Step S3, printing parameter adjustment, add 5000g of thermoplastic polyurethane elastomer (TPU) powder into the printer, spread the powder evenly in the printer, divide the test sample into 5 layers and arrange it in the printer, adjust the printing parameters such as laser power of 48W, scanning spacing of 0.12mm, printing layer thickness of 0.2mm and scanning rate, etc., and adjust the scanning rate so that each layer uses energy density of 0.35, 0.4, 0.45, 0.5, and 0.55j / mm3 respectively, start printing the thermoplastic polyurethane elastomer (TPU) test piece, and test the printed thermoplastic polyurethane elastomer (TPU) test piece; use the mercury injection method to test the porosity of the thermoplastic polyurethane elastomer (TPU) test piece at different energy densities, and find that the porosity decreases with the increase of energy density. Therefore, by adjusting the scanning rate to control the energy density, it is possible to print thermoplastic polyurethane elastomer (TPU) parts with different porosities. The thermoplastic polyurethane elastomer (TPU) test piece with higher porosity shows better air permeability.
[0064] Step S4, printing the mask, adding 250g zinc oxide (ZnO) powder and 4750g thermoplastic polyurethane elastomer (TPU) powder into the powder feeding cylinder for compaction, closing the printer, filling with nitrogen, adjusting the printing parameters, the outer structural surface is the overall structural surface of the mask, the air permeability effect should be obvious, setting the laser power of the outer structural surface to 48W, the scanning spacing to 0.12mm, the printing layer thickness to 0.2mm, and the scanning rate to 4444mm / s; the inner structural surface is cut, and the cutting area is provided with a lattice structural surface, and the lattice structural surface is air permeable through multiple air ducts. Except for the part in the cutting area, the other parts have relatively low requirements for air permeability, and the inner structural surface is in direct contact with human skin, so it is necessary to ensure the surface smoothness of the mask, and set the laser power of the inner structural surface The rate is 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 4000mm / s; the lattice structure surface can fit the human body surface well, is comfortable, and can avoid the mask from pressing the nose and chin, and the lattice structure surface is provided with multiple air ducts, which can promote the circulation of air and achieve breathability. Therefore, the lattice structure surface does not need to consider the porosity. The laser power of the lattice structure surface is set to 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 3636mm / s. After the nitrogen filling is completed, the mask is started to be printed. After the printing is completed, the mask is taken out from the printer, and the residual powder on the surface of the mask is cleaned, and it is put into the sandblasting machine for sandblasting for 15 minutes. After the cleaning is completed, a 3D printed UVA-proof mask is obtained.
[0065] Example 4
[0066] A 3D printed waterproof and UVA and UVB resistant mask comprises the following steps:
[0067] Step S1, designing a mask, using a 3D contour scanner to scan the user's facial contour to obtain facial information, designing a mask that fits the user's face in the three-dimensional software Rhino, adjusting the size, and editing to obtain a mask that fits the user's face;
[0068] Step S2, printing preparation, adding titanium dioxide (TiO2) powder to ethanol aqueous solution, ultrasonic treatment and stirring, adding silane coupling agent KH550 dropwise and maintaining at 70°C for 4 hours, the mass ratio of silane coupling agent KH550: water: anhydrous ethanol is 1:2:50, then stirring, condensing and refluxing at 70°C for 5 hours, washing the obtained product with distilled water, filtering 3 times, and vacuum drying at 60°C for 24 hours to constant weight, to obtain surface functionalized titanium dioxide (TiO2) powder;
[0069] The dried titanium dioxide (TiO2) powder is placed in a ball mill and ball-milled at a speed of 400 r / min for 45 min, and the titanium dioxide (TiO2) powder obtained by ball milling is sieved with a fine sieve to obtain titanium dioxide (TiO2) powder with a particle size of 10 to 100 μm after surface modification;
[0070] Zinc oxide (ZnO) powder is added to an ethanol aqueous solution, ultrasonically treated and stirred, silane coupling agent KH550 is added dropwise, maintained at 75°C for 4 hours, and then stirred and condensed and refluxed at 70°C for 4 hours, the mass ratio of silane coupling agent KH550: water: anhydrous ethanol is 1:2:50, the product is washed with distilled water, filtered three times, and vacuum dried at 60°C for 24 hours to constant weight, to obtain surface functionalized titanium dioxide (TiO2) powder or zinc oxide (ZnO) powder;
[0071] The dried zinc oxide (ZnO) powder is placed in a ball mill and ball-milled at a speed of 400 r / min for 45 minutes, and the zinc oxide (ZnO) powder obtained by ball milling is sieved with a fine sieve to obtain a surface-modified zinc oxide (ZnO) powder with a particle size of 10 to 100 μm;
[0072] Thermoplastic polyurethane elastomer (TPU) powder is placed in a drying oven for drying at a temperature of 50° C. for a drying time of 20 min, and then the dried thermoplastic polyurethane elastomer (TPU) powder is placed in a ball mill for ball milling at a speed of 400 r / min for 20 min; the obtained thermoplastic polyurethane elastomer (TPU) powder is then sieved with a fine sieve to obtain thermoplastic polyurethane elastomer (TPU) powder with a particle size of 20 μm to 100 μm;
[0073] Weigh 250g of modified titanium dioxide (TiO2) powder, 250g of modified zinc oxide (ZnO) powder and 4500g of thermoplastic polyurethane elastomer (TPU) powder, stir and blend a total of 5000g of powder with a stirrer for 30min to fully stir the modified titanium dioxide (TiO2) powder, modified zinc oxide (ZnO) powder and thermoplastic polyurethane elastomer (TPU) powder to obtain a 5% modified titanium dioxide (TiO2) and 5% modified zinc oxide powder. A mixed powder of zinc (ZnO) with hydrophobicity was added to the printer, the mixed powder was evenly spread in the printer, a sample with a size of 80*50*2mm was arranged in the printer, and a test piece was printed using an energy density of 0.45j / mm3. The printed test piece was tested, and the test results showed that the test piece with 5% modified titanium dioxide (TiO2) powder and 5% modified zinc oxide (ZnO) powder added had an SPF value of 50.
[0074] Step S3, printing parameter adjustment, add 5000g of thermoplastic polyurethane elastomer (TPU) powder into the printer, spread the powder evenly in the printer, divide the test sample into 5 layers and arrange it in the printer, adjust the printing parameters such as laser power of 48W, scanning spacing of 0.12mm, printing layer thickness of 0.2mm and scanning rate, etc., and adjust the scanning rate so that each layer uses energy density of 0.35, 0.4, 0.45, 0.5, and 0.55j / mm3 respectively, start printing the thermoplastic polyurethane elastomer (TPU) test piece, and test the printed thermoplastic polyurethane elastomer (TPU) test piece; use the mercury injection method to test the porosity of the thermoplastic polyurethane elastomer (TPU) test piece at different energy densities, and find that the porosity decreases with the increase of energy density. Therefore, by adjusting the scanning rate to control the energy density, it is possible to print thermoplastic polyurethane elastomer (TPU) parts with different porosities. The thermoplastic polyurethane elastomer (TPU) test piece with higher porosity shows better air permeability.
[0075] Step S4, printing the mask, adding 250g of modified titanium dioxide (TiO2) powder, 250g of modified zinc oxide (ZnO) powder and 4750g of thermoplastic polyurethane elastomer (TPU) powder into the powder feeding cylinder for compaction, turning off the printer, filling with nitrogen, adjusting the printing parameters, the outer structural surface is the overall structural surface of the mask, the air permeability effect should be obvious, setting the laser power of the outer structural surface to 48W, the scanning spacing to 0.12mm, the printing layer thickness to 0.2mm, and the scanning rate to 4444mm / s; the inner structural surface is cut, and the cutting area is provided with a lattice structural surface, and the lattice structural surface is breathable through multiple air ducts. Except for the part in the cutting area, the other parts have relatively low requirements for air permeability, and the inner structural surface is in direct contact with human skin, so it is necessary to ensure the surface smoothness of the mask, and set the inner The laser power of the layer structure surface is 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 4000mm / s; the lattice structure surface can fit the human body surface well, has good comfort, can avoid the mask from squeezing the nose and chin, and the lattice structure surface is provided with multiple air ducts, which can promote air circulation and achieve breathability. Therefore, there is no need to consider the porosity of the lattice structure surface. The laser power of the lattice structure surface is set to 48W, the scanning interval is 0.12mm, the printing layer thickness is 0.2mm, and the scanning rate is 3636mm / s. After the nitrogen filling is completed, the mask is started to be printed. After the printing is completed, the mask is taken out of the printer, and the remaining powder on the surface of the mask is cleaned, and it is put into the sandblasting machine for sandblasting for 15 minutes. After the cleaning is completed, a 3D printed waterproof and UVA and UVB-proof mask is obtained.
[0076] Tensile strength and elongation at break analysis
[0077] The tensile strength and elongation at break of the test pieces printed in step S2 of Examples 2 to 4 were analyzed, and the results are summarized in Table 1. It was found that except for the changes in the SPF value of these test pieces, other basic performance tests, such as tensile strength and elongation at break, did not show a significant weakening in strength.
[0078] Table 1 Tensile strength and elongation at break data
[0079] TPU <![CDATA[TPU+TiO2]]> TPU+ZnO <![CDATA[TPU+TiO2+ZnO]]> Tensile strength / MPa 4.5 4.0 4.1 4.5 Elongation at break / % 410 403 396 405
[0080] Porosity analysis of thermoplastic polyurethane elastomer (TPU) test pieces obtained with different printing parameters
[0081] The porosity of the TPU test pieces obtained by using different printing parameters in step S3 of Examples 2 to 4 was analyzed, and the results are summarized in Table 2. The laser power, scanning spacing and printing layer thickness in the printing parameters are consistent, while the scanning rates are different. The energy density can be made different by adjusting the scanning rate. It is found that the porosity of the thermoplastic polyurethane elastomer (TPU) test piece decreases with the increase of energy density. The thermoplastic polyurethane elastomer (TPU) test piece with higher porosity shows better air permeability. Therefore, by adjusting the scanning rate to control the energy density, thermoplastic polyurethane elastomer (TPU) printed parts with different porosities can be realized, thereby adjusting different printing parameters according to the characteristics of different areas of the mask to realize the printing of the mask.
[0082] Table 2 Porosity data of TPU test pieces
[0083] Energy density (j / mm3) 0.35 0.4 0.45 0.5 0.55 Laser power(W) 48 48 48 48 48 Scanning speed (mm / s) 5714 5000 4444 4000 3636 Scanning distance (mm) 0.12 0.12 0.12 0.12 0.12 Print layer thickness (mm) 0.2 0.2 0.2 0.2 0.2 Porosity 44% 41% 35% 30% 24%
Claims
1. A method for 3D printing a waterproof sunscreen mask, characterized in that: The steps include: Step S1, designing a mask, using an instrument to scan the user's facial contour to obtain facial information, designing a mask that fits the user's face in the software, adjusting the size, and editing to obtain a mask that fits the user's face; Step S2, printing preparation, preparing printing powder, stirring and blending the printing powder with a stirrer to obtain a mixed powder, determining whether the mixed powder meets the printing requirements, and then printing a test piece on a 3D printer, adding the mixed powder to the printer, spreading the mixed powder evenly in the printer, arranging the sample in the printer, starting to print the test piece using energy density, and testing the printed test piece; Step S3, adjusting printing parameters, adding polymer material powder into the printer, spreading the powder evenly in the printer, arranging the test sample into 5 layers in the printer, adjusting printing parameters, starting to print the polymer material test piece, and testing the printed polymer material test piece; Step S4, printing the mask, adding the printing powder into the powder feeding cylinder and compacting it, closing the printer, filling with nitrogen, adjusting different printing parameters according to the characteristics of different areas of the mask, and starting gradient printing of the mask after the nitrogen filling is completed. After the printing is completed, the mask is taken out of the printer, and the remaining powder on the surface of the mask is cleaned, and the mask is put into the sandblasting machine for sandblasting. After the cleaning is completed, a 3D printed waterproof and sunscreen mask is obtained.
2. The method for 3D printing a waterproof sunscreen mask according to claim 1, characterized in that: In step S1, the instrument is a 3D contour scanner; the software is the three-dimensional software Rhino; In step S2, the powder is stirred and blended with a stirrer for 30 to 60 minutes; the repose angle and rolling angle of the mixed powder must meet the printing fluidity requirements; the size of the sample is 80*50*2mm; the energy density is 0.35 to 0.55j / mm³; In step S3, the polymer material powder is thermoplastic polyurethane elastomer powder; the size of the test sample is 10*10*10mm; the printing parameters include laser power, scanning spacing, printing layer thickness and scanning rate, etc.; In step S4, the time for sandblasting in the sandblasting machine is 15 minutes.
3. The method for 3D printing a waterproof sunscreen mask according to claim 2, characterized in that: In step S2, when the printing powder is titanium dioxide powder and thermoplastic polyurethane elastomer powder, the titanium dioxide powder accounts for 1-5% of the mixed powder; when the printing powder is zinc oxide powder and thermoplastic polyurethane elastomer powder, the zinc oxide powder accounts for 1-5% of the mixed powder; when the printing powder is treated modified zinc oxide powder, modified titanium dioxide powder and thermoplastic polyurethane elastomer powder, the modified zinc oxide powder and modified titanium dioxide powder each account for 1-5% of the mixed powder.
4. The method for 3D printing a waterproof sunscreen mask according to claim 3, characterized in that: When the printing powder is a treated modified zinc oxide powder, a modified titanium dioxide powder and a thermoplastic polyurethane elastomer powder, the treatment method is to add the titanium dioxide powder or zinc oxide powder to an ethanol aqueous solution, perform ultrasonic treatment and stir, add a coupling agent dropwise and maintain, then stir, condense and reflux, wash the obtained product with distilled water, filter it 3 times, and vacuum dry it at 60° C. for 24 hours to constant weight to obtain a surface functionalized titanium dioxide powder or zinc oxide powder; put the dried titanium dioxide powder or zinc oxide powder into a ball mill for ball milling, and sieve the titanium dioxide powder or zinc oxide powder obtained by ball milling with a fine sieve to obtain a surface-modified titanium dioxide powder or zinc oxide powder with a particle size of 10 to 100 μm; The thermoplastic polyurethane elastomer powder is placed in a drying oven for drying, and then the dried thermoplastic polyurethane elastomer powder is placed in a ball mill for ball milling; then the obtained thermoplastic polyurethane elastomer powder is sieved with a fine sieve to obtain a thermoplastic polyurethane elastomer powder with a particle size of 20 to 100 μm.
5. The method for 3D printing a waterproof sunscreen mask according to claim 4, characterized in that: After adding the coupling agent, the temperature is maintained at 70-80°C for 3-6 hours; the temperature of the stirring, condensing and reflux is 70°C, and the time is 3-6 hours; the coupling agent is a silane coupling agent KH550, and the mass ratio of silane coupling agent: water: anhydrous ethanol is 1:2:50; the ball milling speed of the titanium dioxide powder or zinc oxide powder in the ball mill is 400r / min, and the ball milling time is 30-60min; the drying temperature of the thermoplastic polyurethane elastomer powder in the drying oven for drying treatment is 40-60°C, and the drying time is 10-30min; the ball milling speed of the thermoplastic polyurethane elastomer powder in the ball mill is 400r / min, and the ball milling time is 10-30min.
6. A 3D printed waterproof sunscreen mask, made by the method for printing a 3D waterproof sunscreen mask according to any one of claims 1 to 5, characterized in that: It comprises an elastic structural surface (1) and a lattice structural surface (2); the lattice structural surface (2) is arranged on the elastic structural surface (1); a plurality of air ducts are arranged in the lattice structural surface (2); and the lattice structural surface (2) is capable of fitting to the surface of a human body.
7. The 3D printed waterproof sunscreen mask according to claim 6, characterized in that: The elastic structural surface (1) comprises an outer structural surface (11) and an inner structural surface (12); the outer structural surface (11) and the inner structural surface (12) are tightly fitted; the inner structural surface (12) is cut to obtain a cutting area; the lattice structural surface (2) is arranged on the cutting area; and the inner structural surface (12) is in direct contact with human skin.
8. The 3D printed waterproof sunscreen mask according to claim 7, characterized in that: The lattice structure plane (2) comprises a first lattice structure plane (21) and a second lattice structure plane (22); the first lattice structure plane (21) and the second lattice structure plane (22) are arranged opposite to each other; the first lattice structure plane (21) and the second lattice structure plane (22) are arranged at two ends of the inner layer structure plane (12); the first lattice structure plane (21) is in contact with a human nose; and the second lattice structure plane (22) is in contact with a human chin.
9. The 3D printed waterproof sunscreen mask according to claim 7, characterized in that: The elastic structural surface (1) further comprises fixing belts (13); the fixing belts (13) are arranged at both ends of the outer structural surface (11).
10. The 3D printed waterproof sunscreen mask according to claim 7, characterized in that: The air permeability of the outer structural surface (11) is higher than the air permeability of the inner structural surface (12).